"The Adequacy of their Attention": Gender-Bias and the Incorporation of Feminist Perspectives in the Australian Introductory Law Subject - Helen Ward (Legal Education Review)
When issues of diversity are raised in a law topic, they often appear — or will be regarded by the students — as not central to the substantive legal or doctrinal aspects of the topic. Thus, a preliminary teaching question which arises is the specialisation/mainstream debate: should such material be presented in a separate segment of the topic (ie: specialisation) in order to give it some overt visibility, or should it be “mainstreamed” by including references to it throughout the topic? Either approach can lead to marginalisation, as we see students putting down their pens or not attending class where such material is going to be covered. The approach I have attempted to take in teaching evidence is to show how such issues of diversity are not marginal, but central, by: considering diversity from the very beginning, as embedded in the fundamental evidentiary questions of relevance and the logic of proof; referring to race and gender issues in a range of evidentiary contexts; having at least one specialist section which focuses intensively on diversity; and including consideration of race and gender in assessment.